(untitled) (Al-Academy, 2024)
The study aims to make modifications to a theory for calculating glaze components, which was developed by the German chemist H. Seger (1839-1893 AD) 130 years ago which was named after him. It is still effective even with the current scientific and technological development and the emergence of electronic programs for glaze calculations that relied on the basics of this theory. This theory has been subjected to a number of modifications, and there are still shortcomings in some of its applications. In this research, two “modifications” were made in the first one, the glaze ) Formula unit) was liberated from the constants of molar equivalent values and to facilitate the addition of components of any value while in the second modification, a mechanism was developed to calculate opacity with earthen alkaline (RO) and acidic oxides (RO2), the theory in showing opacification was limited to amphoteric substances (R2O3), and in application, the modifications showed their effectiveness